2019
DOI: 10.1371/journal.pone.0224965
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical determination of the HIV-1 matrix shell structure and its impact on the biology of HIV-1

Abstract: Since its discovery in the early 1980s, there has been significant progress in understanding the biology of type 1 human immunodeficiency virus (HIV-1). Structural biologists have made tremendous contributions to this challenge, guiding the development of current therapeutic strategies. Despite our efforts, there are unresolved structural features of the virus and consequently, significant knowledge gaps in our understanding. The superstructure of the HIV-1 matrix (MA) shell has not been elucidated. Evidence b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Ellipsoidal shapes were more affected than spherical shapes because of the more drastic change in angles starting from the initial tile ( Figure 1 B,C, yellow tile). In a previously published Supplemental Figure S2 [ 14 ], we showed that regular hexagons could not be used to build the HIV model unless one of the hexagon sides had a shorter side length.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ellipsoidal shapes were more affected than spherical shapes because of the more drastic change in angles starting from the initial tile ( Figure 1 B,C, yellow tile). In a previously published Supplemental Figure S2 [ 14 ], we showed that regular hexagons could not be used to build the HIV model unless one of the hexagon sides had a shorter side length.…”
Section: Resultsmentioning
confidence: 99%
“…Scripts and calculations: All scripts and calculations were developed in the python language as previously described [ 14 ]. Coordinates were exported to PyMol for the construction of structures.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations